Retail Availability of Delta-8 THC Near Schools, Fort Worth, Retail Availability of Delta-8 THC Near Schools, Fort Worth, Texas, 2021 - Amanda Y. Kong; Cassidy R. LoParco; Lily Herbert; Andrew Yockey; Matthew E. Rossheim (Health Behavior Research)
Delta-8 THC (D8) is an intoxicating compound linked to poisonings and hospitalizations, and no federal laws prohibit its sale to minors. We examined retail D8 availability near public schools (n=231) in Fort Worth, Texas, where D8 sales are minimally regulated. Between September- October 2021, trained data collectors collected D8 availability data from 1,178 retailers with alcohol, tobacco, and/or consumable hemp licenses. We examined differences in product availability for retailers near (within 0.5 miles) schools vs. not near schools. There was a higher prevalence of retailers selling D8 near (vs. not near) schools (12.4% vs. 8.2%; chi-square test 5.84, p<0.05). Of the 231 public schools, 37.2% (n=86) had at least one D8 retailer nearby. Of the 86 schools with D8 retailers nearby, the cheapest products were for vaping (40.7%) and edibles (31.4%). There were school-level racialized and socioeconomic inequities in availability. Ongoing surveillance of D8 availability and laws are urgently needed.